Implementation of an Overall Design of a Flexible Manufacturing System. (2015) - Erdin, M. Emin; Atmaca, Alper
Abstract: In this study, an implementation of the design of an FMS is performed to calculate necessary number, utilization and sequence of workstations and plant layout for given production quantities of different parts, processing sequence and times. Analytical bottleneck model and rank order clustering techniques are used in the calculation and analysis of the system. Manufacturing cells are constituted for similar parts to simplify the analysis of the system and to efficient use of workstations. Results are compared with the conventional manufacturing conditions to determine the effectiveness of the implementation.